2009
DOI: 10.4103/0256-4947.51818
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to a healthy lifestyle among patients attending primary care clinics at a university hospital in Riyadh

Abstract: BACKGROUND AND OBJECTIVES:The occurrence and progress of chronic non-communicable diseases (NCDs) is associated with unhealthy lifestyles and behaviors. Modification of barriers to healthy lifestyle can produce great benefits. The objective of this study was to identify barriers to physical activity and healthy eating among patients attending primary health care clinics in Riyadh city.PATIENTS AND METHODS:A cross-sectional study was conducted at King Khalid University Hospital (KKUH) in Riyadh city. Four hundr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
112
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(129 citation statements)
references
References 11 publications
(13 reference statements)
11
112
4
Order By: Relevance
“…This indicates how hard it is to maintain a healthy diet in Saudi Arabia, where social connections are strong and people are expected to attend all social gatherings to which they are invited to eat the traditional food provided (15). This is similar to the situation in the Philippines, where the people have a strong connection with rice as a source of carbohydrate (16).…”
Section: Self-care Management Practicesmentioning
confidence: 86%
“…This indicates how hard it is to maintain a healthy diet in Saudi Arabia, where social connections are strong and people are expected to attend all social gatherings to which they are invited to eat the traditional food provided (15). This is similar to the situation in the Philippines, where the people have a strong connection with rice as a source of carbohydrate (16).…”
Section: Self-care Management Practicesmentioning
confidence: 86%
“…1,20 The socio-demographic context of low income and education contribute to the perception of the existence of obstacles to adherence, given that these factors are hindering the adoption of healthier habits. 3,19 Population studies on the individual factors associated with the use of medical consultations by adults show similar results to those found in this study, with greater participation of females, individuals from lower income backgrounds, Followed all of the guidelines given for a time and then gave up 21 12.4…”
Section: Discussionmentioning
confidence: 99%
“…Goston et al (2012) noted that occupational categories may show differences in health-related behaviours such as diet and physical activity that contribute to chronic disease. Apart from occupational categories, various studies have identified a range of psychological, environmental and social factors that may influence an individual's readiness to engage in healthy eating and regular physical activity (Burton and Turrell, 2000;AlQuaiz and Tayel, 2009;Nomura et al, 2010). Among workers, the most common barriers to healthy diet at the individual level are lack of willpower (AlQuaiz and Tayel, 2009) and the cost of healthy foods (Pawlak and Colby, 2009).…”
Section: Introductionmentioning
confidence: 99%